Prophylactic Use of Continuous Norepinephrine at a Dose of 0.05 mcg/kg BW/min in Spinal Anaesthesia for Cesarean Section Patients in Ketapang - Rachman, Abdul (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2024)
Background: Norepinephrine infusion decreases hypotension after spinal anesthesia during a cesarean section. There is an increasing attitude toward using norepinephrine to prevent spinal hypotension. There hasn't been much investigation on the use of norepinephrine in spinal anesthesia in Indonesia, particularly for cesarean sections in rural areas.Methods: In this single-blinded norepinephrine group. Randomized clinical trial: The norepinephrine group was given continuous norepinephrine before spinal anesthesia. Parturients for elective and emergency cesarean section were allocated to receive norepinephrine infusion (0.05 mcg/kg BW/mnt. Our primary outcome was the incidence of hypotension within 36 min of spinal anesthesia administration. Secondary outcomes included side effects such as nausea, vomiting, and chills during surgery.Result: In total, 92 patients were enrolled. Of these patients included in the ﬁnal analysis. Patients who suffered hypotension showed hypotension at minute zero and minute twelve (14.13 %), minute twenty-four (13.04 %), and minute thirty-six (18.47 % )—the frequency of chills and nausea/vomiting. Three (3.26 %) and eight (8.89 %) participants in the norepinephrine group reported feeling chills and nausea/vomiting.Conclusion: prophylactic norepinephrine infusion may reduce HR without increasing the risk of post-spinal hypotension following cesarean delivery.